Knowledge and attitudes of parents after the implementation of mandatory vaccination in kindergartens of Palermo, Italy - Restivo, Vincenzo; Palmeri, Sara; Bono, Stefania; Caracci, Francesca; Russo Fiorino, Giusy; Foresta, Angelo; Gaglio, Valerio; Graziano, Giorgio; Marchese, Valentina; Maniglia, Marialuisa; Sannasardo, Claudia; Saporito, Laura; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Even though vaccination is easy to access in Europe, it has been facing several outbreaks caused by vaccine preventable diseases. Trying to balance the right to health of the community with individual self-determination, in Italy was mandate vaccination for ten vaccine preventable diseases in 2017. The project “Sportello Vaccinale” provided a counseling service to parents in kindergarten of Palermo. The main objective of the study was to investigate knowledge and compliance on vaccination by children’s parents after the implementation of mandatory vaccination. Methods: A cross sectional study was conducted among parents accessing to the “Sportello Vaccinale” using a questionnaire.  The questionnaire consisted of 34 items divided into three sections: socio-demographic data; knowledge and attitude on mandatory vaccination using Health Belief Model (HBM); Health Literacy (HL) level. Results: A total of 95 questionnaires were garnered in the kindergartens from respondents with a mean age of 36 (±SD=6) years. The respondents who delayed hexavalent or Measles, Mumps, Rubella and Varicella (MMRV) vaccinations were 8 (8%) and the more frequent cause was fear of adverse reaction (87%). The sample had more often high level of health literacy (37%), and 55% had higher HBM score. The factor significantly associated with higher HBM score was the age of respondents (OR= 1.14, p=0.006) after controlling for other variables. Conclusions: Consent to vaccination practice was widely represented, but the results of the study highlighted the need for parents to have more information and more time devoted to the practice of vaccination counseling. Implementing counseling activities at school or at the vaccination service, could support an aware decision process of the parents on vaccination topic.